Communicating science, not magic - Brooke N. Macnamara; Alexander P. Burgoyne; David Moreau (Communications Psychology)
When communicating psychological intervention research, two pernicious tendencies have become prominent: using imprecise terms with lay meanings and sensationalizing outcome descriptions. This Comment examines the consequences of these communication styles and proposes strategies for effective communication, ensuring enthusiasm does not come at the cost of credibility.